Making innovation policy work learning from experimentation - Dutz, Mark A.; Kuznetsov, Yevgeny; Lasagabaster, Esperanza; Pilat, Dirk (OECD, 2014)
This book explores emerging topics in innovation policy for more inclusive and sustainable growth, building on concrete examples. It develops the notion of experimental innovation policy - which integrates monitoring and feedback at the policy design stage, and occurs continuously to improve impact and implementation. This approach should help improve the quality and efficiency of public expenditures supporting innovation policy. Experimental policy making is particularly important for new and emerging innovation domains, where the scope for learning and improvement is the greatest. To make the discussion as concrete and relevant as possible for practitioners and policy makers, three emerging domains of innovation policy are explored in greater detail: innovative entrepreneurship, green innovation, and pro-poor or base-of-the-pyramid (BoP) innovation.